“Ultramodern times”: consequences of smartphone use on workers (Research, Society and Development, 2021)
The ubiquitous and timeless use of smartphones in the workplace has contributed to a rise in musculoskeletal disorders. Objective: To identify the symptoms regarding workers' health as a result of the use of smartphones in the workplace. Methods: Quantitative-cross-sectional study of workers from south of Brazil through online social networks. A questionnaire composed of socioeconomic, device use behavior inside and outside of work and the presence of musculoskeletal symptoms questions were applied. Data were submitted to statistical analysis and association tests. Results: 326 individuals answered and 196 constituted the sample. They are predominantly females (61.54%), incomplete higher education (47.18%), monthly income of up to two salary wages (45.64%), reported always used their smartphone (62% ) and perceived it as necessary for their professional performance (55.9%). There was no evidence of association between the daily use of the smartphone and the presence of symptoms conditioned to physical activity. However, the study found that the lower the income, the longer the use of the device during off-hours (P = .0281), even to work. Conclusion: Smartphone is a recent technology, social adjustments are still being negotiated, but lack of regulations of how and when to use it inside and outside work, are discussions that emerge from this context.